Cannibalism in bears - Allen, Maximilian L.; Krofel, Miha; Yamazaki, Koji; Emmarie P., Alexander; Koike, Shinsuke (Ursus, 2022)
Bears are the largest terrestrial carnivores, and most bear species can be characterized as opportunistic omnivores. An infrequent foraging tactic for bears is cannibalism, where a bear consumes a conspecific individual, either through scavenging or following intraspecific predation. Although several reports of cannibalism events are known, no attempt has been made so far to gather the available information to analyze for general patterns. We therefore performed a systematic literature review to understand patterns of cannibalism in bears. We documented 39 studies detailing 198 cannibalism events. We only found evidence of cannibalism in 4 of the 8 bear species, with more events reported for polar bears (Ursus maritimus n = 107, 54.0%) than for all other species combined. Cannibalism was most frequently associated with infanticide (n = 66, 33.3%) and conspecific strife (n = 30, 15.2%), both of which were more frequent among males than females. The most common apparent reason for cannibalism among predators is to increase fitness (i.e., eating a conspecific increases nutrition, whereas killing reduces competition for resources), but is also often linked to sexually selected infanticide in bears. Cannibalism most often appears to be an opportunistic consumption of an available carcass and not directly connected with the primary cause of death. As such, cannibalism in bears may be more casual and opportunistic than a behavior that evolved as a life history strategy.